Management of Testicular Silicone Gel-Filled Prosthesis Rupture: Case Report of a Rare Event and a Review of the Literature - Quang-Bao Phan; Nicolas Koutlidis; Céline Duperron; Eric Mourey; Frédéric Michel; Luc Cormier (Case Reports in Urology)
Introduction. We report a case of spontaneous rupture of a single testicular prosthesis in a patient who had undergone bilateral orchiectomy and silicone gel-filled prosthesis insertion. The consequences of this rare event are discussed. There is no management algorithm. Case Presentation. A 55-year-old man presented to our outpatient department with altered consistency in his right testicular prosthesis and a painful right hemiscrotum with no systemic symptoms thirty-three years after the implantation of the prosthesis. We removed this implant without replacement, in accordance with the patient’s wishes. Conclusion. The long time between the implantation and the spontaneous rupture is remarkable and was never before described. The removal of the prosthesis was straightforward and it would have been possible to implant a new prosthesis after taking into account the condition of the skin.